We Don’t Know What We Want”: The Ups and Downs of Global Travel in Dave Eggers’s You Shall Know Our Velocity (2002) - Małgorzata Rutkowska (Anglica. An International Journal of English Studies)
Dave Eggers’s You Shall Know Our Velocity (2002) can be read as a (post) modern voice in the ongoing debate on educational, transformative and redemptive po- tential of foreign travel for the young Americans in the late 1990s. The article focuses on representation of global travel experience in the novel employing American Old World journey conventions on the one hand and tourism-travel dichotomy on the other. The backpackers in Eggers’s novel can be characterized as drifters. Their encounters with otherness most often result in confusion. All in all, the novel downplays the role of travel in the globalized, homogenized world at the turn of the 21st century.